Maternal serum lead levels and risk of preeclampsia in pregnant women: a cohort study in a maternity hospital, Riyadh, Saudi Arabia - Jameil, Noura Al (e-Century Publishing Corporation, 2014)
Preeclampsia is one of the major cause of maternal morbidity and mortality. Despite numerous studies, the etiology of preeclampsia has not yet been fully elucidated. There has been confliction in results on the role of maternal lead in preeclampsia. Keeping in view with the scarcity of data on role of lead in preeclamptic women of Saudi Arabia and the disparity in earlier findings, the present study was carried out to determine the levels of maternal serum lead in patients with preeclampsia in comparison to normal pregnancy. The study consisted of 120 pregnant women divided into three groups of 40 each, control, HR group and PET group. The serum levels of lead were estimated by Inductively coupled plasma optical emission spectrometry. We found that the mean value of serum lead was 18.23 ± 2.34, 20.08 ± 2.15 and 27.18 ± 2.13 µg/dl in control, high risk group and preeclamptic group respectively. The levels of Pb were found to decrease significantly (P < 0.05) in preeclamptic group compared to control. However, there was no significant change in levels of Pb when HR group was compared to Control and preeclamptic group. In the present study, we observed that serum levels of lead were positively correlated with systolic and diastolic blood pressure and were statistically significant (P < 0.05). However, negative correlation was observed between Pb and BMI ruling out the association of BMI with preeclampsia. It is thus concluded that preeclampsia is associated with significant increase in maternal lead and these increasing levels of serum lead pose a significant risk in pregnant women to preeclampsia.